Artificial Intelligence to Determine Fetal Sex - Frisch, Emily H.; Jain, Anant; Jin, Mike; Duhaime, Erik P.; Malshe, Amol; Corey, Steve; Allen, Robert; Duggan, Nicole M.; Fischetti, Chanel E. (American Journal of Perinatology, 2024)
Objective This proof-of-concept study assessed how confidently an artificial intelligence (AI) model can determine the sex of a fetus from an ultrasound image.Study Design Analysis was performed using 19,212 ultrasound image slices from a high-volume fetal sex determination practice. This dataset was split into a training set (11,769) and test set (7,443). A computer vision model was trained using a transfer learning approach with EfficientNetB4 architecture as base. The performance of the computer vision model was evaluated on the hold out test set. Accuracy, Cohen's Kappa and Multiclass Receiver Operating Characteristic area under the curve (AUC) were used to evaluate the performance of the model.Results The AI model achieved an Accuracy of 88.27% on the holdout test set and a Cohen's Kappa score 0.843. The ROC AUC score for Male was calculated to be 0.896, for Female a score of 0.897, for Unable to Assess a score of 0.916, and for Text Added a score of 0.981 was achieved.Conclusion This novel AI model proved to have a high rate of fetal sex capture that could be of significant use in areas where ultrasound expertise is not readily available.Key Points
Keywords: artificial intelligence; machine learning; ultrasound; fetal sex